Peran Mediasi Dari Inovasi Karyawan Pada Hubungan Antara Internet Banking Dan Kinerja Karyawan - Meidiyanty, Elvira; Ramli, Abdul Haeba; Mariam, Siti (Universitas Nusa Putra, 2023)
This quantitative research analyzes the influence of Internet banking and employee innovation on employee performance. Data analysis in this study used the Structural Equation Modeling (SEM) method. With Smart-PLS software, the population in this study was private banking employees in Jabodetabek with a sample of 120 using purposive sampling with the criteria of remote bank employees having worked in the private sector for at least one year. The study results show that Internet banking positively affects employee performance. In contrast, internet banking has a positive effect on employee innovation and employee innovation, and employee turnover positively affects employee performance.